2015
DOI: 10.2965/jwet.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

Development of UASB-DHS System for Treating Industrial Wastewater Containing Ethylene Glycol

Abstract: This study evaluated the performance of a novel treatment system consisting of an upflow anaerobic sludge blanket (UASB) and a downflow hanging sponge (DHS) for the treatment of industrial wastewater containing 8% ethylene glycol and 2% propylene glycol discharged from a rubber production unit. The system achieved high COD removal (91 ± 4.3%) and methane recovery (82 ± 20%) at an organic loading rate of 8.5 kg-COD/(m 3 ·day). The UASB allowed an organic loading rate of 14 kg-COD/(m 3 ·day) with a constant hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…40 g COD/L/d. Moreover, compatible with the results of this particular study; Watari et al. (2015) also reported ca.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…40 g COD/L/d. Moreover, compatible with the results of this particular study; Watari et al. (2015) also reported ca.…”
Section: Resultssupporting
confidence: 92%
“…40 g COD/L/d. Moreover, compatible with the results of this particular study; Watari et al (2015) also reported ca. 91% COD removal with 82% methane recovery at a high-rate anaerobic reactor fed by industrial wastewater including 8% ethylene-and 2%…”
Section: Reactor Performances At Increased Propylene Glycol Concentrasupporting
confidence: 92%
See 3 more Smart Citations